2015
DOI: 10.1002/ajim.22503
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time fatigue reduction in emergency care clinicians: The SleepTrackTXT randomized trial

Abstract: Background We assessed performance characteristics and impact of a mobile phone text-message intervention for reducing intra-shift fatigue among emergency clinician shift workers. Methods We used a randomized controlled trial of 100 participants. All participants received text-message assessments at the start, every 4-hours during, and at end of scheduled shifts over a 90-day period. Text-message queries measured self-rated sleepiness, fatigue, and difficulty with concentration. Additional text-messages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…One intrashift intervention used text messages to perform momentary assessments of EMS workers while they were on-shift. Interventional messages were sent if employees reported severe fatigue, sleepiness or difficulty with concentration 36. Participants were highly compliant, and the intervention reduced fatigue and sleepiness in a subgroup of participants.…”
Section: Discussionmentioning
confidence: 99%
“…One intrashift intervention used text messages to perform momentary assessments of EMS workers while they were on-shift. Interventional messages were sent if employees reported severe fatigue, sleepiness or difficulty with concentration 36. Participants were highly compliant, and the intervention reduced fatigue and sleepiness in a subgroup of participants.…”
Section: Discussionmentioning
confidence: 99%
“…The logistical challenges associated with PVT measurement of a mobile workforce like air‐medical clinicians are significant. Deficits in performance among EMS clinicians are believed to occur during the mid‐point to end of shifts that last greater than 12 h—specifically between midnight and 0500 . Future investigations should design their protocol to include multiple measures of PVT performance, yet weigh the cost versus benefits when determining the total number of measurements per shift.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for allowing multiple participations and limiting total participations to two include: (1) our pool of potentially eligible participants was limited to four study sites and (2) minimal information would be gained with more than two participations by any one individual under the same shift duration. Our calculation was based on the following assumptions: (1) complete start and end of shift PVT data from each participant for at least one shift during the study period and (2) a 20% rate of attrition across study sites, which is of a similar level observed in previous research . Findings are presented in tables stratified by the number of times a participant had participated in this study (once or twice).…”
Section: Methodsmentioning
confidence: 99%
“…This is the second study of its kind to use mobile phone text messages as a vehicle to conduct real-time assessment and intervention of a unique clinician population [7, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…2) [7, 9]. We have added additional single-item assessments to occur between scheduled shifts (inter-shift).…”
Section: Methodsmentioning
confidence: 99%